2010
DOI: 10.1177/1352458510374202
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of self-assessed fatigue and alertness in multiple sclerosis

Abstract: The alertness subtest of the Test of Attentional Performance may offer an objective method of evaluating self-reported fatigue, and may therefore - in addition to the Fatigue Severity Scale - be a suitable tool for the assessment of multiple sclerosis patients complaining of fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 37 publications
4
53
3
4
Order By: Relevance
“…There was no evidence of measuring fatigability before and after a demanding task. Other studies have used a similar approach 22,24 . The theory and construct underpinning such methods is not clear.…”
Section: Challenges With Existing Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no evidence of measuring fatigability before and after a demanding task. Other studies have used a similar approach 22,24 . The theory and construct underpinning such methods is not clear.…”
Section: Challenges With Existing Measuresmentioning
confidence: 99%
“…The fact that some of the studies listed in Table 1 have used varied study designs and metrics that are inconsistent with existing operational definitions may be a symptom of this problem. For example, Parmenter et al tested pwMS during periods of high, and relatively low, self-reported fatigue over two separate testing periods on different days 8 , and similar to other studies 22,24 , did not assess a decline in either information processing speed, reaction time or accuracy over time on continuous performance task, or probe task given before and immediately after completing a demanding cognitive task 1,5 , nor explicitly define how they operationalised cognitive fatigability 8,24 .…”
Section: Challenges With Existing Measuresmentioning
confidence: 99%
“…17 However, studies that tried to quantify the incidence of cognitive impairment in patients with MS showed large inconsistencies ranging from 5.5% of a cohort exhibiting cognitive impairment 18 to 59.7%. 19 The differences are probably due to the diverse methodology used to measure cognitive function.…”
Section: Patient-reported Outcomes Focussed On the Expectations Of Pamentioning
confidence: 99%
“…With the increasing recognition of MS as a progressive neurodegenerative disease from the very beginning, it is questionable whether relapse rate and inflammatory lesions on brain MRI (variables in the suggestive term 'freedom of disease activity') that have been applied in the CLARITY study and other recent large Phase III MS trials are still adequate measures for the evaluation of new MS therapies. 'Freedom of disease activity' disregards other relevant aspects of the disease, such as progressive brain atrophy, cognitive dysfunction, sleep disorders and fatigue [20][21][22][23] --factors that may have a substantial negative impact on the patients' quality of life [24]. New potential surrogate markers, such as optical coherence tomography, are emerging that may prove useful to monitor neurodegeneration and neuroprotection in MS trials [25,26].…”
mentioning
confidence: 99%